Financial frictions, durable goods and monetary policy - Ugochi T. Emenogu; Leo Michelis (Bank of Canada, 2019)
This paper examines the effect of financial frictions on the consumption of durables and non-durables in a two-sector dynamic stochastic general equilibrium (DSGE) model with sticky prices and heterogeneous agents. The financial frictions are a combination of loanto- value (LTV) and payment-to-income (PTI) constraints faced by borrowers. In this setting, a monetary contraction drastically reduces the maximum amount consumers can borrow to purchase durable goods. As a result, the model predicts that the consumption of durables falls, along with non-durables, even when durable prices are fully flexible. Also, output falls and the nominal interest rate increases following monetary tightening. Thus, our model's predictions better match the data than models in existing literature.
Keywords: E44; E52; 330; Monetary policy; Financial system regulation and policies